The Scolari. Counterpoints of university life (brawls, books, and libertas) - Benedusi, Alessandro (CIAN-Revista de Historia de las Universidades, 2026)
This panel delves into the multifaceted and often volatile existence of the Paduan scholares during the sixteenth and seventeenth centuries, a period where the pursuit of high culture frequently collided with the rowdy reality of the city’s streets. Through a close reading of contemporary chronicles and university acts, the narrative reconstructs the delicate equilibrium between the cherished ideal of patavina libertas and the explosive “town and gown” tensions that repeatedly tested civic order. Beyond the anecdotes of revelry and violence, this analysis underscores the profound economic and political synergy between the Studium and the Republic of Venice. Ultimately, it reveals the student body not merely as a transient population, but as a dynamic, disruptive, and indispensable force that shaped the social and cultural identity of early modern Padua.
Keywords: Early Modern university history; academic privileges; town and gown relations; urban conflict and social identity